Neurological complications following pediatric allogeneic hematopoietic stem cell transplantation: Risk factors and outcome - Zaidman, Irina; Shaziri, Tamar; Averbuch, Dina; Even-Or, Ehud; Dinur-Schejter, Yael; NaserEddin, Adeeb; Brooks, Rebecca; Shadur, Bella; Gefen, Aharon; Stepensky, Polina (Frontiers in Pediatrics, 2022)
Background: Allogeneic hematopoietic stem cell transplantation (HSCT) is an efficient treatment for numerous malignant and non-malignant conditions affecting children. This procedure can result in infectious and non-infectious neurological complications (NCs). Objective: To examine the incidence, risk factors and outcomes of NCs in pediatric patients following allogeneic HSCT. Methods: We performed a retrospective study of 746 children underwent 943 allogeneic HSCTs in 2 large pediatric hospitals in Israel from January 2000 to December 2019. Results: 107 pediatric patients (14.3%) experienced 150 NCs. The median follow-up was 55 months. Non-infectious NCs were more common than infectious NCs (81.3% vs 18.7%). Factors significantly associated with type of NC (infectious versus non-infectious) were underlying disease (immunodeficiency versus malignant and metabolic/ hematologic disease) (p-value=0.000), and use of immunosuppressive agent, either Campath or ATG (p-value=0.041). Factors with a significant impact on developing neurological sequelae post-NC were number of HSCT >1 (p-value=0.028), Alemtuzumab as an immunosuppressive agent (p-value=0.003), and infectious type of NC (p-value=0.046). Overall survival of whole NC-cohort was 44%; one-third of all mortality cases were attributed to the NC. The strongest prognostic factors associated with mortality were older age at HSCT (p-value=0.000), Alemtuzumab as an immunosuppressive agent (p-value=0.004) and existence of neurological sequelae (p-value=0.000). Abnormal CNS imaging (p-value=0.013), Alemtuzumab as an immunosuppressive agent (p-value=0.019) and neurological sequelae (p-value=0.000) had a statistically significant effect on neurological cause of death. Conclusion: Infectious and non-infectious NCs are a significant cause of morbidity and mortality following allogeneic HSCT in children. Further research is required to better understand the risk factors for different NCs and their outcomes regarding sequelae and survival.